Validation of PCHE-Type CO2–CO2 Recuperative Heat Exchanger Modeling Using Conductance Ratio Method - Viktoria Carmen Illyés; Francesco Crespi; Xavier Guerif; Andreas Werner (Energies, 2025)
Printed-circuit heat exchangers (PCHEs) are compact exchangers with exceptional heat-transfer properties that are important for supercritical CO2 technology. Recalculating the heat transfer under off-design conditions is a common task. Thus, in this paper, traditional and PCHE-specific correlations are analyzed in a conventional, discretized one-dimensional model using the conductance ratio method. The predicted heat transfer is compared with the experimental data of a CO2–CO2 heat exchanger with zigzag-type channels and one with s-shaped fin channels under various working conditions. The results demonstrate that all selected heat-transfer correlations predicted the transferred heat within +/−20% using the conventional model. The much simpler conductance ratio method yields better results, with heat transfer within +/−10%, even with conservative inputs to the model.